e-Granary Electronic Library: A Panacea for Effective Low-Cost Means of Knowledge and Lecture Delivery for Distance Learning in the National Open University of Nigeria - Okonkwo, Lucy Ndidiamaka (West African Journal of Open and Flexible Learning, 2023)
e-Learning is virtual learning process in which a learner stays in one place and explores as well as interacts with knowledge anywhere and at any time through electronic means. This e-learning is first choice for distance education. The electronic library also known as digital library, an online library, an Internet library, a digital repository, or a digital collection will be a great support to e- learning. This digital library embraces an online database of digital objects that can include text, still images, audio, video, digital documents, or other digital media formats to be accessible through the Internet. The accessibility of this information digitally in university libraries could be expensive. The remedy could be to embrace the use of the egranary Digital Libra ry which is an offline information store that provides instant access to digital resources for those lacking adequate Internet connections. A single e-Granary, connected to a wired or wireless local area network (LAN) helps to solve the situation. The research work investigates the concept of e-Granary Digital Library and its usefulness for developing distance education especially in the rural areas of Nigeria, features of e-Granary digital library, e-Granary Digital Library Implementation, benefits of e-Granary Digital Library to the development of distance learning, steps for using digital library for executing distance learning education, importance of e-Granary Digital Library for the development of distance learning programmes and problems of e- Granary digital as a mode of lecture delivery, conclusion and recommendations were made. Résumé : La formation en ligne est un processus d'apprentissage virtuel dans lequel l'apprenant reste à un endroit et explore et interagit avec la connaissance n'importe où et à n'importe quel moment par le biais de moyens électroniques. L'apprentissage en ligne est le premier choix pour l'enseignement à distance. La bibliothèque électronique, également connue sous le nom de bibliothèque numérique, bibliothèque en ligne, bibliothèque Internet, dépôt numérique ou collection numérique, sera d'un grand secours pour l'apprentissage en ligne. Cette bibliothèque numérique englobe une base de données en ligne d'objets numériques qui peuvent inclure du texte, des images fixes, de l'audio, de la vidéo, des documents numériques ou d'autres formats de médias numériques accessibles par l'intermédiaire de l'internet. L'accessibilité de ces informations sous forme numérique dans les bibliothèques universitaires pourrait s'avérer coûteuse. La solution pourrait être d'adopter l'utilisation de la bibliothèque numérique e-Granary, qui est un magasin d'information hors ligne offrant un accès instantané aux ressources numériques pour ceux qui ne disposent pas de connexions Internet adéquates. Le travail de recherche étudie le concept de bibliothèque numérique e-Granary et son utilité pour le développement de l'enseignement à distance, en particulier dans les zones rurales du Nigeria, les caractéristiques de la bibliothèque numérique e-Granary, la mise en œuvre de la bibliothèque numérique e-Granary, les avantages de la bibliothèque numérique e-Granary pour le développement de l'enseignement à distance, les étapes de l'utilisation de la bibliothèque numérique pour l'exécution de l'enseignement à distance, l'importance de la bibliothèque numérique e-Granary pour le développement du programme d'enseignement à distance et les problèmes de la bibliothèque numérique e-Granary en tant que mode de transmission des cours, une conclusion et des recommandations ont été formulées.. Mots-clés : L'apprentissage à distance, le Réseau Local sans Fil, Les Etudes à Distance, la Rentabilité, Bibliothèque Numérique e-Grenier